Menguak Strategi Manajemen Talenta Hotel Berbintang di Bali - Brany Ferushita Dewi; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
Business competition in this globalization and digital era is very tight. General Managers & Human Resources Leaders face their own challenges. To work around this, qualified and highly qualified Human Resources are needed to be able to give the best contribution to the company, especially to respond to competition that arises in the business, especially related to the availability of talented employees. This study aims to obtain information about the implementation of Talent Management that has been carried out by star hotels in Bali. This research is exploratory research with a qualitative approach. The total number of respondents was 16 people consisting of 3 people from Prime Plaza Hotel & Suites Sanur-Bali, 4 people from Capella Ubud, 3 people from Swan Paradise a Pramana Experience, 3 people from Four Seasons Resort Bali, and 3 people from Mercure. Bali Legion. Where the selection of respondents represents a variety of hotel management, including hotels managed internationally (international chained hotels) and nationally (national chained hotels), 4 and 5 star categories. The application of Talent Management in hotels has a significant impact on producing competent and qualified Human Resources to support the increase in the company's competitiveness against its competitors. Another positive result is that the level of loyalty from employees to the company also increases. As was the case with the Capella Ubud Hotel, where their employees decided to resign because of a promotion, a better offer to cruise ship management, or abroad. The results obtained are that Talent Management is very important to do, because this system is effective and efficient in increasing employee competence, which will then increase the company's competitiveness against its competitors. Likewise with the Four Seasons Resort Bali, after the pandemic, many young people joined, and they joined the Four Seasons to see opportunities abroad. There have been quite a lot of employee transfers to overseas branches.